Andragogically Building a Doctor of Andragogy Program - Susan K. Isenberg; John A. Henschke (Adult Education Research Conference, 2013)
Developing and implementing a Doctor of Andragogy Program andragogically provides an opportunity to ‘think outside the box’. It requires congruency between talking and action. Is this possible to accomplish? Stay tuned.